COVID-19 Pandemic and its Impact on Tourism Industry in Nepal - Ulak, Nimesh (Journal of Tourism & Adventure, 2020)
The article aims to measure the impact of novel corona virus disease (COVID-19) pandemic on tourism industry in Nepal. The pause of tourism mobility for months due to an abrupt halt of transportation means; shuttered borders; and stay-at-home orders by government has brought adverse effects on Nepal’s tourism industry and its stakeholders. Likewise, airlines, accommodation, transport operators and other sub-sectors of Nepal are suffering due to international travel bans. There are spillover impacts of the pandemic on the socio-cultural structure, human psychology and global economic system where tourism industry is no exception. The impacts are gradually unfolding. Hence, the study also focuses on the preparedness and response strategy of stakeholders for combating this pandemic which has brought crisis and fear to Nepal’s tourism industry. The research is qualitative in its nature and followed basic/fundamental research type to expand knowledge on this topic which will shed light on the significant impact on the tourism industry in Nepal. The study is based on both primary data collected through interviews with intended stakeholders and the review of several relevant secondary sources.